The Effect of Visceral Abdominal Fat Volume on Oxidative Stress and Proinflammatory Cytokines in Subjects with Normal Weight, Overweight and Obesity - García-Sánchez A (Dove Medical Press, 2020)
Andrés García-Sánchez, Jorge Iván Gámez-Nava, Elodia Nataly Díaz-de la Cruz, Ernesto Germán Cardona-Muñoz, Itzel Nayar Becerra-Alvarado, Javier Alejandro Aceves-Aceves, Esther Nérida Sánchez-Rodríguez, Alejandra Guillermina Miranda-Díaz Department of Physiology, University Health Sciences Centre, University of Guadalajara, Guadalajara, Jalisco, MexicoCorrespondence: Alejandra Guillermina Miranda-DíazDepartment of Physiology, University Health Sciences Centre, University of Guadalajara, Guadalajara, Jalisco, MexicoEmail kindalex1@outlook.comPurpose: The increase of visceral abdominal fat (VAF) and oxidative stress (OS) are independent predictors for cardiovascular risk. This study aimed to determine the association of VAF with proinflammatory cytokines, oxidants, antioxidants, and oxidative damage to DNA in subjects with normal weight, overweight, and obesity.Patients and Methods: A cross-sectional study that included 21 men and 71 women who attended for a medical check-up was conducted. Dual-energy X-ray absorptiometry (DXA) was used to measure the VAF volume. ELISA and colorimetric techniques were used for chemical analysis.Results: Low activity of superoxide dismutase (SOD) was found in overweight and obese subjects compared to the normal weight group (p=0.005). In contrast, the activity of glutathione peroxidase (GPx) was higher in the overweight and obesity groups compared to the normal weight subjects (p=0.017). The total antioxidant capacity (TAC) was also increased in the overweight group compared to the normal weight group (p=0.04). According to the volume of VAF, the levels of tumor necrosis factor alfa and interleukin 6 showed no differences between subjects with normal and high VAF. Subjects with high VAF show higher levels of 8-isoprostans compared to normal VAF group (p=0.039). Less concentration of 8-oxoguanine-DNA-N-glycosylase-1 (hOGG1) was found in the high VAF group (p=0.032) compared to the normal VAF subjects. VAF was positively correlated with lipoperoxides (LPO) (r=0.27, p< 0.05) and 8-isoprostanes (r=0.25, p< 0.05). We also found correlations between oxidative stress markers and anthropometric ratios for intra-abdominal fat. The waist-hip ratio was positively correlated with LPO (r=0.30, p< 0.05) and TAC (r=0.24, p< 0.05).Conclusion: These findings suggest that the predominantly oxidative damage associated with VAF in overweight or obesity is lipoperoxidation and oxidative DNA damage. Alterations in endogenous antioxidant defenses may not be linked to the amount of VAF.Keywords: oxidative stress, oxidative DNA damage, antioxidant enzymes, Lunar iDXA, visceral fat cutoff score